What to focus on in order to accelerate access to modern energy services and energy use efficiency in Bangladesh - United Nations Economic; Social Commission for Asia; the Pacific; Hasan Mahmud; Joyashree Roy (Asia-Pacific Sustainable Development Journal, 2023)
How can a rapidly growing country, such as Bangladesh, overcome the barriers to realizing Sustainable Development Goal 7? The present study includes an analysis of the barriers to achieving 24x7 access to modern energy and the required improvements to make energy more efficient to overcome them in Bangladesh. Interpretive structural modeling (ISM) is applied to identify the interactions among the barriers as laid out in context-relevant scientific literature. The Cross-impact matrix multiplication applied to classification (MICMAC) is applied to classify the barriers. The results indicate that the barriers can be addressed through a systematic packaging and prioritization approach.